Experimental study of the effect of restraining rim design on the extreme behavior of pendulum sliding bearings. (19th November 2017) - Bao, Yu; Becker, Tracy C.; Sone, Takayuki; Hamaguchi, Hiroki
Summary: While the performance of sliding isolators has been extensively validated under typical levels of ground motion, there have been very few experimental studies on the extreme behavior of sliding isolation bearings when the displacement limit is reached. However, to appropriately design isolated systems, from selecting the displacement capacity of the bearing to sizing the superstructure members, the behavior of the bearing as it reaches, and in some cases exceeds, the displacement limit should be well understood. A series of shake table tests to investigate the extreme behavior of double pendulum sliding bearings under strong ground motions were conducted at McMaster University. One major difference in sliding bearings around the world is how the motion of the bearing is restrained at the bearing's displacement capacity. Scaled bearings with four different types of restraining rim designs were included, representing typical sliding restraining rims found in Europe, Japan, and the United States. Experimental observation shows that the restraining rim has a significant influence on the extreme behavior of sliding isolation bearing. Key response parameters such as impact force and uplift are evaluated and compared between the different sliding bearing designs. While the bearing with no rim bearing imparts the lowest forces to the superstructure, it loses its functionality at a lower amplitude input than all the other rim types. For the other rim designs, the impact forces are significantly higher but they remained operational although damaged.